Analysis of the Influence of Human Resources, Natural Resources and Infrastructure Resources on Sectoral Development Policies in Soziona Tourism Economic Area (Somi Bozihona-Onolimbu Nalawo) Nias Regency, North Sumatra Province, Indonesia - Yarman Gulo; Sirojuzilam; Badaruddin; Agus Purwoko (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study is to analyze the influence of human resources, natural resources and infrastructure resources on sectoral development policies in the Soziona tourism economic area, Nias Regency, North Sumatra Province. The research was conducted in the Soziona tourism economic area, Nias Regency, North Sumatra Province, namely Gido District, Idanogawo District, and Bawolato District. The analytical method used in this study uses the Partial Least Square Structural Equation Modeling (PLS-SEM) approach with SmartPLS v.3.0 software. The results show that (1) human resources (SDM) have a positive and significant effect on sectoral development policies (KPS), (2) natural resources (SDA) have a positive and significant effect on sectoral development policies (KPS), (3) resources Infrastructure resources (SDSP) have a positive and significant effect on sectoral development policies (KPS, (4) human resources (SDM) have a positive and significant effect on natural resources (SDA) and (5) human resources (SDM) have a positive and significant impact on significant to infrastructure resources (SDSP).